An introduction to Object-Oriented programming with Java™ - Wu, C. Thomas (McGraw-Hill, 2004)
An Introduction to Object-Oriented Programming with Java provides an accessible and technically thorough introduction to the basics of programming using java. Objects are used early so that students think in objects right from the beginning...